Feasibility Analysis of Inpari IR Nutri Zinc Rice Seed Farming in Irrigated Paddy Fields in Riau Province - Nurhayati, Nurhayati; Fahri, Anis; Yusuf, Rachmiwati; H Sinaga, Parlin; Widyanto, Hery; Zuhdi, Fadlan; Masganti, Masganti; Lenin, Ismon; Meilin, Araz; Yuliani, Nurmili; et al. (KnE Social Sciences, 2024)
Rice variety Inpari IR Nutri Zinc is a type of rice that can be used to overcome stunting problems in Indonesian children, so it needs to be produced more. The production of this rice requires information on the financial feasibility of agricultural products so that it is attractive for cultivation on a more massive basis. This activity aims to determine the feasibility of farming the Inpari IR Nutri Zinc rice. A variety which is cultivated using (a) rice transplanter machine (Transplanter), (b) direct paddy planting with rice seeder (Atabela), (c) hand planting rice (Manual), as well as the level of profit from farmers’ income in the form of harvested dry grain (HDG), milled dry grain (MDG), and candidate rice seeds. The research was carried out in irrigated rice fields in Bunga Raya Village, Siak Regency, Riau Province by 3 cooperators each in a plot of 1 hectare. Observations were made on plant growth, yield production, production costs, revenues, profits, andrevenue cost ratio (RCR). Farming feasibility analysis is calculated using the RCR formula. The results showed that the plant height ranged from 92.7-99.9 cm and the number of productive tillers was 16-19 stems/clump. Changes in product form from HDG to MDG, and rice seed show increased production costs, revenues, profits, and RCR. The highest revenue (IDR 34,400,000 ha−1) and profit (IDR 17,750,000 ha−1), with a CRC of 2.07, was obtained from the transplanter planting method with the product form of rice seed. Keywords: Inpari IR Nutri Zinc, revenue cost ratio, production feasibility